2013
DOI: 10.1364/oe.21.017392
|View full text |Cite
|
Sign up to set email alerts
|

Controllable double tunneling induced transparency and solitons formation in a quantum dot molecule

Abstract: We consider the coupling effect between interdot tunneling coupling and external optical control field to study the linear optical property and the formation of temporal optical solitons in a quantum dot molecules system, analytically. The results show that the double tunneling induced transparency (TIT) windows are appeared in the absorption curve of probe field because of the formation of dynamic Stark splitting and quantum destructive interference effect from the two upper levels. Interestingly, the width o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…where In order to describe the propagation characteristics of the generated FWM, the motion equations must be simultaneously solved with Maxwell's equation in a self-consistent manner. [31] Under a slowly varying envelope approximation, we obtain…”
Section: Modelmentioning
confidence: 99%
“…where In order to describe the propagation characteristics of the generated FWM, the motion equations must be simultaneously solved with Maxwell's equation in a self-consistent manner. [31] Under a slowly varying envelope approximation, we obtain…”
Section: Modelmentioning
confidence: 99%
“…[36,37] This is similar to the EIT effect in a three-level ultra-cold atomic medium. She et al [38] studied the linear optical and Kerr nonlinear properties of double QD system. They found that there exist two transparent windows and the type of the optical soliton can also be controlled by changing the intensity of the control field.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the previous researches in which optomechanical systems are coupled with different objects like membranes, atoms [27], and many interesting phenomena in QDMs [28,29] are studied, we consider in this paper, an optomechanical system with a Fabry-perot cavity consisting of a mechanical resonator and three-level QDMs. Two output fields are introduced in the cavity with different frequency, where the one field provides the tunneling strength in the QDMs.…”
Section: Introductionmentioning
confidence: 99%